Transient gene and microRNA expression profile changes of confluent human fibroblast cells in spaceflight. Issue 6 (25th February 2016) - Zhang, Ye; Lu, Tao; Wong, Michael; Wang, Xiaoyu; Stodieck, Louis; Karouia, Fathi; Story, Michael; Wu, Honglu
ABSTRACT: Microgravity, or an altered gravity environment different from the 1 g of the Earth, has been shown to influence global gene expression patterns and protein levels in cultured cells. However, most of the reported studies that have been conducted in space or by using simulated microgravity on the ground have focused on the growth or differentiation of these cells. It has not been specifically addressed whether nonproliferating cultured cells will sense the presence of microgravity in space. In an experiment conducted onboard the International Space Station, confluent human fibroblast cells were fixed after being cultured in space for 3 and 14 d, respectively, to investigate changes in gene and microRNA (miRNA) expression profiles in these cells. Results of the experiment showed that on d 3, both the flown and ground cells were still proliferating slowly, as measured by the percentage of Ki‐67 + cells. Gene and miRNA expression data indicated activation of NF‐k B and other growth‐related pathways that involve hepatocyte growth factor and VEGF as well as the down‐regulation of the Let‐7 miRNA family. On d 14, when the cells were mostly nonproliferating, the gene and miRNA expression profile of the flight sample was indistinguishable from that of the ground sample. Comparison of gene and miRNA expressions in the d 3 samples, with respect to d 14, revealed that most of the changes observed on d 3 were related to cell growth for both the flown and ground cells. Analysis of cytoskeletal changes via immunohistochemistry staining of the cells with antibodies for α‐tubulin and fibronectin showed no difference between the flown and ground samples. Taken together, our study suggests that in true nondividing human fibroblast cells in culture, microgravity experienced in space has little effect on gene and miRNA expression profiles.—Zhang, Y., Lu, T., Wong, M., Wang, X., Stodieck, L., Karouia, F., Story, M., Wu, H. Transient gene and microRNA expression profile changes of confluent human fibroblast cells in spaceflight. FASEB J. 30, 2211–2224 (2016). www.fasebj.org